Flexural behaviour of superelastic shape memory alloy reinforced concrete beams during loading and unloading stages. (15th February 2019) - Elbahy, Yamen Ibrahim; Youssef, Maged A.
Highlights: Flexural behaviour of SMA RC beams during loading and unloading is investigated. A simplified sectional analysis method is developed, validated and adopted. Flexural behaviour of SMA RC beams is investigated through a parametric study. Equations to estimate optimum amount and length of SMA bars are provided. Abstract: Trend of using smart structures, which can adjust when exposed to severe unexpected loading, is increasing. One of the methods to achieve such structures relies on smart materials. For example, replacing conventional steel reinforcing bars in Reinforced Concrete (RC) structures with superelastic Shape Memory Alloy (SMA) bars significantly reduces the residual deformations caused by post-yielding behaviour. This paper provides in-depth understanding of the flexural behaviour of SMA RC beams. A sectional analysis method, which predicts the flexural behaviour of SMA RC beams during both loading and unloading stages, is adopted and validated using available experimental data. An extensive parametric study is then carried out to investigate the effect of different geometrical properties. Recommendations for the optimum amount and length of SMA bars are drawn based on results of this study.